1959
DOI: 10.1002/app.1959.070010206
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of high molecular weight acetal resins

Abstract: Stable, high molecular weight polymers of formaldehyde have been studied to determine their molecular structure. The polymer chain was shown to be a polyoxymethylene by chemical analysis and infrared absorption spectra. Infrared techniques also revealed hydroxyl end groups which were replaced by acetate groups on esterification. The endgroups, which were also measured by chemical methods, were used to determine the number‐average molecular weight over the range 20,000 to 98,000. Values obtained by assuming two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
3

Year Published

1959
1959
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 4 publications
2
12
1
3
Order By: Relevance
“…However, there is a newly discovered mechanism for the copolymerization of TOX and DOX, using BF 3 O(Et) 2 as catalyst in the presence of nanosilica, the copolymerization give a polymer with two or more consecutive DOX units in an oxymethylene main-chain sequence, 37 which differ from the previous results of Yamasaki. 38 However, the macromolecular chain of acetal/silica nanocomposite had only one DOX unit in an oxymethylene mainchain.…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…However, there is a newly discovered mechanism for the copolymerization of TOX and DOX, using BF 3 O(Et) 2 as catalyst in the presence of nanosilica, the copolymerization give a polymer with two or more consecutive DOX units in an oxymethylene main-chain sequence, 37 which differ from the previous results of Yamasaki. 38 However, the macromolecular chain of acetal/silica nanocomposite had only one DOX unit in an oxymethylene mainchain.…”
Section: Introductioncontrasting
confidence: 49%
“…Various investigators have presented two methods for determining the comonomer content: gas chromatography 29,30 and NMR spectroscopy. [31][32][33] The ring-opening copolymerization of TOX can be initiated by Lewis acid such as BF 3 O(Et) 2 , TiCl 4,34 and CH 3 COClO 4 . 35 Penczek and coworkers 36 studied the solution copolymerization of TOX and a small amount of DOX initiated by BF 3 O(n-Bu) 2 and found that the unstable fraction content of the copolymer increased with increasing conversion, indicative of a higher reactivity of DOX than that of TOX toward the copolymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weights of the polymers may be measured in dimethylformamide as described in a companion paper. 14 Comparisons by the thermal stability tests show the polymers prepared in these investigations to be more stable than those obtained by procedures in the literature. Results are summarized in Table 111.…”
Section: Thermal Stabilitymentioning
confidence: 92%
“…IR-spectroscopic methods have been described for the determination of terminal groups in acetylated homopolymers [144,145].…”
Section: Quality Specifications and Analysismentioning
confidence: 99%